Splatoon. Squid kids comedy show. Vol. 4 - Goto, Hideki, 1974-; Turnage, Bryant (VIZ Media, LLC, 2021)
Contains a collection of graphic novel stories that follow the adventures of Inklings Hit, Maika, and Kou, members of the Squid Kids Comedy Show.